Dimorphism and hydrocarbon metabolism in Yarrowia lipolytica var. indica - Palande, A. S.; Kulkarni, S. V.; Leon-Ramirez, C.; Campos-Gongora, E.; Ruiz-Herrera, J.; Deshpande, Mukund V. (Archives of Microbiology, 2014)
Yarrowia lipolytica is able to metabolize high Mr hydrophobic natural compounds such as fatty acids and hydrocarbons. Characteristically, strains of Y. lipolytica can grow as populations with variable proportions of yeast and filamentous forms. In the present study, we describe the dimorphic characteristics of a variant designated as Y. lipolytica var. indica isolated from petroleum contaminated sea water and the effect of cell morphology on hydrocarbon metabolism. The variant behaved as a yeast monomorphic strain, under conditions at which terrestrial Y. lipolytica strain W29 and its derived strains, grow as almost uniform populations of mycelial cells. Using organic nitrogen sources and N-acetylglucosamine as carbon source, var. indica was able to form mycelial cells, the proportion of which increased when incubated under semi-anaerobic conditions. The cell surface characteristics of var. indica and W29 were found to be different with respect to contact angle and percent hydrophobicity. For instance, percent hydrophobicity of var. indica was 89.93 +/- A 1.95 while that of W29 was 70.78 +/- A 1.1. Furthermore, while all tested strains metabolize hydrocarbons, only var. indica was able to use it as a carbon source. Yeast cells of var. indica metabolized hexadecane with higher efficiency than the mycelial form, whereas the mycelial form of the terrestrial strain metabolized the hydrocarbon more efficiently, as occurred with the mycelial monomorphic mutant AC11, compared to the yeast monomorphic mutant AC1.
Keywords: Hexadecane metabolism; Yarrowia lipolytica; Yeast-mycelium transition

Determination of the effect of polyamines on an oil-degrading strain of Yarrowia lipolytica using an odc minus mutant - Campos-Gongora, E.; Palande, A. S.; Leon-Ramirez, C.; Pathan, E. K.; Ruiz-Herrera, J.; Deshpande, M. V. (Fems Yeast Research, 2018)
Yarrowia lipolytica is an ascomycetous dimorphic yeast with immense potential for industrial applications, including bioremediation of crude oil-contaminated environments. It has been shown that a dimorphic marine isolate of Y. lipolytica (var. indica) has significant capacity to degrade fatty acids and alkanes, when in its yeast morphology. It has also been demonstrated that polyamines play an important role in the yeast-to-mycelium transition of different strains of Y. lipolytica that are unable to utilize those carbon sources. To determine the role of polyamines on their capacity to utilize oils and hydrocarbons, on the dimorphic transition, and also on other characteristics of the var. indica strain of Y. lipolytica, we proceeded to obtain ornithine decarboxylase minus (odc(-)) mutants. These mutants behaved as yeasts independently of the concentrations of putrescine added. Further, they conserved the oil-degrading capacity of the parent strain. The odc(-) mutant can thus be used in fatty acid degradation, and oil spill remediation with distinct advantages.